2016
DOI: 10.1080/10498850.2015.1073204
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Adsorption Isotherms and Thermodynamic Properties of Penaeus vannamei Meat with and without Maltodextrin Addition

Abstract: Moisture adsorption isotherms of freeze-dried Penaeus vannamei meat containing maltodextrin (PV-MD) and maltodextrin free (PV) samples were determined at temperatures of 5, 15, 25, 35, and 45°C with water activity (a w ) ranging from 0.113 to 0.931. The adsorption behaviors of PV and PV-MD followed type III isotherms. The equilibrium moisture content of PV and PV-MD decreased with increasing temperature and increased with increasing a w . The monolayer moisture content increased with the addition of maltodextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Pacific white shrimp ( Penaeus vannamei ), generally known as Litopenaeus vannamei , is indigenous to the Pacific coast of Central and South America from Mexico to Peru (Ketnawa et al., ; Nimrat, Boonthai, & Vuthiphandchai, ; Sookying, Davis, & Silva, ; Xie et al., ). Because of its rapid growth, disease tolerance, high survival rate, strong environmental adaptability, and great economic value, Pacific white shrimp have become the most popular aquaculture shrimp in Asia, the Pacific Islands, and North and South America (Comoglio, Amin, Roque, Anguas, & Haro, ; Mingyan et al., ; Nimrat et al., ; Yang, Wu, Jian, & Zhang, ; Zhou, Wang, Wang, & Tan, ), and its yield is the highest among the three largest cultured penaeid shrimp species in the world (Shi, Lin, Zhao, Zhang, & Wang, ; Yang, Xie, Niu, Liu, & Tian, ). It contains high protein, well‐balanced essential amino acids, highly unsaturated fatty acids, mineral elements, vitamins, and other nutrient substances that greatly contribute to human health (Ketnawa et al., ; Qian et al., ; Shi et al., ; Shi, Lin, Zhao, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacific white shrimp ( Penaeus vannamei ), generally known as Litopenaeus vannamei , is indigenous to the Pacific coast of Central and South America from Mexico to Peru (Ketnawa et al., ; Nimrat, Boonthai, & Vuthiphandchai, ; Sookying, Davis, & Silva, ; Xie et al., ). Because of its rapid growth, disease tolerance, high survival rate, strong environmental adaptability, and great economic value, Pacific white shrimp have become the most popular aquaculture shrimp in Asia, the Pacific Islands, and North and South America (Comoglio, Amin, Roque, Anguas, & Haro, ; Mingyan et al., ; Nimrat et al., ; Yang, Wu, Jian, & Zhang, ; Zhou, Wang, Wang, & Tan, ), and its yield is the highest among the three largest cultured penaeid shrimp species in the world (Shi, Lin, Zhao, Zhang, & Wang, ; Yang, Xie, Niu, Liu, & Tian, ). It contains high protein, well‐balanced essential amino acids, highly unsaturated fatty acids, mineral elements, vitamins, and other nutrient substances that greatly contribute to human health (Ketnawa et al., ; Qian et al., ; Shi et al., ; Shi, Lin, Zhao, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…During storage, it is prone to occurring the melanosis (discoloration), strong endogenous enzyme activity, lipid oxidation, protein denaturation, and a loss of gelling and water‐holding functionality in shrimp (Nileshprakash et al. ; Qian et al., ; Shi et al., ; Shi et al., ). Therefore, much specific attention should be focused on the control of moisture content without falling off in quality in order to extend the shelf life of shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the moisture sorption process for all tested films within the examined moisture ranges was considered as enthalpy-driven, because the T β values were much higher than the T hm value. It was reported that enthalpy-controlled behaviors depend upon food ingredients; nevertheless, entropy-controlled behaviors rely mainly on the microstructure of the matrix [22]. These observations imply that the microstructure of the GG-based films was stable in the process of moisture sorption within the temperature range from 5 to 25 • C. Furthermore, the addition of glycerol and nisin merely altered the chemical composition of GG film, and did not alter its microstructure.…”
Section: Enthalpy-entropy Compensation Theorymentioning
confidence: 94%
“…Triplicate film samples were placed into airtight desiccators and equilibrated with various saturated salt solutions to obtain a w ranging from 0.113 to 0.931 [20,21], and the values are shown in Table 1. The desiccators were put into incubators with set temperatures (viz., 5 The moisture sorption isotherm data of GG-based films were fitted to Guggenheim-Anderson-De Boer (GAB) (Equation (1)) and the Halsey model (Equation (2)) [22].…”
Section: Moisture Sorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation